An eco-friendly protocol for synthesis of thiourea derivatives: 1-benzoyl-3-benzylguanidine and 1-benzoyl-3-benzyl-O-ethylisourea. A possible non-purely thermal microwave assisted reaction - Marquez, H.; Loupy, A.; Calderon, O.; Perez, E. R. (Elsevier B.V., 2006)
1-Benzoyl-3-benzylguanidine and 1-benzoyl-3-benzyl-O-ethylisourea were synthesized in good yields (68 and 76%, respectively) from 1-benzoyl-3-benzylthiourea and benzoyl-ethylthiocarbamate in dry media conditions using KF-Al2O3 under microwave irradiation. Strong nucleophilic amines promoted the sulfur elimination by attack on the thiocarbonyl group in both thiourea and thiocarbamates to afford guanidines and isourea, respectively. Transesterification products were obtained from p-TsOH catalyzed reaction of thiocarbamate with alcohols under MW-solvent-free conditions. Very important non-purely thermal MW specific effects were evidenced and attributed to stabilization by coulombic interactions between materials and waves. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: 1-benzoyl-3-benzylguanidine; 1-benzoyl-3-benzyl-O-ethylisourea; thiocarbamates; microwave irradiation; solvent-free conditions